Shariah Perspective on Investing in Islamic Capital Market: A Qualitative Study - Muhammad Irkham Firdaus; Mufti Fitiyani (Universitas Muhammadiyah Yogyakarta, 2022)
The capital market is one indicator of economic growth in a country. The capital market development is currently very fast as an alternative to investment for investors. Sharia capital market activities do not conflict with sharia principles in the capital market. The Islamic capital market is universal and can be used by anyone regardless of ethnic background, religion, and race. This study aims to find out how sharia investment benefits elements in the world and in the hereafter, will become the main priority. Therefore, the investment is long-term. Islamic law strongly supports investment activities in the Islamic capital market because it contains the basis of Islamic law referred from the Qur'an, Hadith, Fiqh and the opinions of scholars.